Targeted radionuclide therapy for head and neck squamous cell carcinoma: a review - Sanwick, Alexis M.; Chaple, Ivis F. (Frontiers in Oncology, 2024)
Head and neck squamous cell carcinoma (HNSCC) is a type of head and neck cancer that is aggressive, difficult to treat, and often associated with poor prognosis. HNSCC is the sixth most common cancer worldwide, highlighting the need to develop novel treatments for this disease. The current standard of care for HNSCC usually involves a combination of surgical resection, radiation therapy, and chemotherapy. Chemotherapy is notorious for its detrimental side effects including nausea, fatigue, hair loss, and more. Radiation therapy can be a challenge due to the anatomy of the head and neck area and presence of normal tissues. In addition to the drawbacks of chemotherapy and radiation therapy, high morbidity and mortality rates for HNSCC highlight the urgent need for alternative treatment options. Immunotherapy has recently emerged as a possible treatment option for cancers including HNSCC, in which monoclonal antibodies are used to help the immune system fight disease. Combining monoclonal antibodies approved by the US Food and Drug Administration, such as cetuximab and pembrolizumab, with radiotherapy or platinum-based chemotherapy for patients with locally advanced, recurrent, or metastatic HNSCC is an accepted first-line therapy. Targeted radionuclide therapy can potentially be used in conjunction with the first-line therapy, or as an additional treatment option, to improve patient outcomes and quality of life. Epidermal growth factor receptor is a known molecular target for HNSCC; however, other targets such as human epidermal growth factor receptor 2, human epidermal growth factor receptor 3, programmed cell death protein 1, and programmed death-ligand 1 are emerging molecular targets for the diagnosis and treatment of HNSCC. To develop successful radiopharmaceuticals, it is imperative to first understand the molecular biology of the disease of interest. For cancer, this understanding often means detection and characterization of molecular targets, such as cell surface receptors, that can be used as sensitive targeting agents. The goal of this review article is to explore molecular targets for HNSCC and dissect previously conducted research in nuclear medicine and provide a possible path forward for the development of novel radiopharmaceuticals used in targeted radionuclide therapy for HNSCC, which has been underexplored to date.